Lightweight high-strength heat-resistant refractory high-entropy alloy and preparation method thereof

By regulating the content of TI, ZR or Ti, and V elements and the replacement of MO elements, prepare a low -density single -phase BCC high -entropy alloy, solve the problem of poor molten high entropy alloy density and room temperature plasticity. Excellent mechanical performance at room temperature and high temperature.

CN119351848APending Publication Date: 2025-01-24NANJING TECH UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411490218.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing refractory high entropy alloys have high constituent elements density and easy formation of intermetallic compounds between elements, which lead to brittleness at room temperature, which limits its further development.

Method used

By regulating the content of TI, ZR or Ti, and V elements, the atomic size mismatch of the alloy is increased, and some V elements are replaced through the MO elements to increase the modular mismatch, thereby preparing a low -density single -phase BCC high entropy alloy.

Benefits of technology

It achieves the low density of the alloy, high strength and toughness at room temperature, and high strength and thermal stability at high temperatures, solving the problems of high density and poor room temperature plasticity of refractory high-entropy alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351848A_ABST
    Figure CN119351848A_ABST
Patent Text Reader

Abstract

The invention provides a lightweight high-strength heat-resistant refractory high-entropy alloy and a preparation method thereof, and belongs to the technical field of metal materials and preparation thereof. The light-weight high-strength heat-resistant refractory high-entropy alloy is recorded as TiaZrbVcModNb25 according to the atomic number percentage, a is larger than or equal to 25 and smaller than or equal to 45, b is larger than or equal to 5 and smaller than or equal to 25, c is larger than or equal to 5 and smaller than or equal to 25, d is larger than or equal to 0 and smaller than or equal to 10, and a + b + c + d = 75. By regulating and controlling the content of Ti and Zr or Ti and V elements in the as-cast single-phase refractory high-entropy alloy, the atomic size mismatch of the alloy is increased, so that the alloy shows serious lattice distortion, meanwhile, high-modulus Mo replaces part of V, the modulus mismatch of the alloy is increased, the alloy has low density, high strength and high toughness at room temperature, and the alloy can be widely applied to the field of high-temperature alloy production. And the alloy also shows high strength and thermal stability at high temperature. And the preparation operation of the refractory high-entropy alloy is simple, the preparation is free of pollution, the experimental energy consumption is low, the problems that the refractory high-entropy alloy is relatively high in density, relatively poor in room-temperature plasticity and the like are solved, and the refractory high-entropy alloy has a wide application prospect in the fields of chemical engineering, metallurgy and nuclear power.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal materials and preparation thereof, and in particular to a light, high-strength, heat-resistant, refractory high-entropy alloy and a preparation method thereof. Background Art

[0002] Nickel-based superalloys exhibit good mechanical properties at high temperatures and have been widely used in the manufacture of parts under high-temperature conditions such as aircraft engines and gas turbines. With the advancement of science and technology, the requirements for materials in high-temperature environments are getting higher and higher. The operating temperature of traditional nickel-based alloys is 800-1000℃, which can no longer meet higher working conditions. The emergence of high-entropy alloys provides a new idea for the new generation of superalloy materials. High-entropy alloys are usually composed of 4 or more main elements with equal or similar atomic fractions. High-entropy alloys with unique chemical structures exhibit high mixing entropy, severe lattice distortion, hysteresis diffusion and "cocktail" effect. By optimizing the composition and selecting appropriate processing technology, high-entropy alloys can have a series of excellent properties, such as high hardness, high strength, corrosion resistance, and excellent resistance to high-temperature softening.

[0003] Among various types of high-entropy alloys, refractory high-entropy alloys exhibit excellent high-temperature mechanical properties and are expected to become a new generation of commercial high-temperature alloys. Refractory high-entropy alloys are often composed of elements with a melting point exceeding 1650°C, such as Nb, Mo, Ta, Zr, W, V, Hf and other elements. Since these high-melting point elements have a low valence electron concentration, they are more likely to form a stable BCC structure. The chemical disorder at the atomic scale and the high melting point make refractory high-entropy alloys exhibit high strength, high hardness, and oxidation resistance at high temperatures. However, since high-melting point elements often have a higher density and it is easy to form intermetallic compounds between the constituent elements, most of them are brittle at room temperature, which limits the further development of refractory high-entropy alloys.

[0004] Therefore, how to obtain a lightweight, high-strength, heat-resistant, refractory high-entropy alloy and its preparation method is a technical problem that needs to be solved at present. Summary of the invention

[0005] The purpose of the present invention is to provide a lightweight, high-strength, heat-resistant, refractory high-entropy alloy and a preparation method thereof, which is used to solve the technical problems that the element density of existing high-entropy alloys is high, intermetallic compounds are easily formed between elements, and the alloy is brittle at room temperature.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a light-weight, high-strength, heat-resistant, refractory, high-entropy alloy. The light-weight, high-strength, heat-resistant, refractory, high-entropy alloy is denoted by Ti in terms of atomic percentage. a Zr b V c Mod Nb 25 , where 25≤a≤45, 5≤b≤25, 5≤c≤25, 0≤d≤10 and a+b+c+d=75.

[0008] Furthermore, the lightweight, high-strength, heat-resistant, refractory high-entropy alloy is selected from one of the following alloys:

[0009] Ti 42 VxD 23 2nB 25 、Ti 40 Zr 10 V 20 5nN 25 、Ti 38 Zr 12 V 18 7nB 25 、Ti 34 Zr 25 V9Mo7 25 、Ti 36 Zr 25 V9Mo5 25 .

[0010] The present invention also provides a method for preparing a lightweight, high-strength, heat-resistant, refractory high-entropy alloy, comprising the following steps:

[0011] Take the raw materials in atomic percentage, place them in a crucible from top to bottom for smelting according to their melting points, and smelt them repeatedly N times and then cool them to obtain a lightweight, high-strength, heat-resistant, refractory high-entropy alloy.

[0012] Furthermore, the smelting is carried out under argon protection, and the smelting pressure is -0.03 to -0.01 MPa.

[0013] Furthermore, the smelting power is 90-110 kW.

[0014] Furthermore, N≥5, and the cooling time is 15 to 30 minutes.

[0015] Furthermore, the purity of the raw materials is independently ≥ 99.97%.

[0016] Beneficial effects of the present invention:

[0017] The alloy of the present invention is mainly obtained by adjusting Ti a Zr b V c Mo d Nb 25The content of Ti, Zr or Ti, V elements, Zr element has the largest atomic size (155pm), V element has the smallest atomic size (134pm), as the large atomic size Zr element replaces Ti element or Ti element replaces smaller size V element, the atomic size mismatch of the alloy increases, where the atomic size mismatch can reach up to 5.2%, so that the alloy exhibits severe lattice distortion. At the same time, Mo element has the highest shear modulus (123GPa), which is much higher than other constituent elements (30-50GPa), and Mo and V elements have similar atomic sizes. As the high modulus Mo element replaces a small amount of V element, the modulus mismatch of the alloy is greatly increased, thereby improving the mechanical properties of the alloy. The prepared single-phase refractory high entropy alloy has a low density, the tensile strength of the single-phase cast sample at room temperature can exceed 1050MPa and high toughness (>16%), and it has good thermal stability and high strength at 800℃, with a compressive strength of about 720MPa and a compressive strain of more than 45%.

[0018] The light refractory high entropy alloy of the present invention has a relatively low density of the selected alloying elements. The large atomic size Zr element replaces the Ti element or the Ti element replaces the smaller size V element, and the high modulus Mo element replaces a small amount of V element, forming a single-phase BCC light refractory high entropy alloy, which maintains the toughness of the alloy at room temperature and the high strength and thermal stability at high temperature through solid solution strengthening. The preparation operation of the light refractory high entropy alloy is simple, the preparation is pollution-free, and the experimental energy consumption is low. It also solves the problems of high density and poor room temperature plasticity of refractory high entropy alloys, and has broad application prospects in the fields of chemical industry, metallurgy and nuclear power. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Ti 34 Zr 25 V9Mo7 25 XRD pattern of lightweight, high-strength, heat-resistant, refractory high-entropy alloy;

[0020] Figure 2 Ti 34 Zr 25 V9Mo7 25 Transmission electron microscope image of lightweight, high-strength, heat-resistant, refractory high-entropy alloy;

[0021] Figure 3 Ti 34 Zr 25 V9Mo7 25 Tensile stress-strain curve of lightweight, high-strength, heat-resistant, refractory high-entropy alloy. DETAILED DESCRIPTION

[0022] The present invention provides a light-weight, high-strength, heat-resistant, refractory, high-entropy alloy. The light-weight, high-strength, heat-resistant, refractory, high-entropy alloy is denoted by Ti in terms of atomic percentage. a Zr b V c Mo d Nb 25 , where 25≤a≤45, 5≤b≤25, 5≤c≤25, 0≤d≤10 and a+b+c+d=75.

[0023] In the present invention, a is preferably 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45.

[0024] In the present invention, b is preferably 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, or 25.

[0025] In the present invention, c is preferably 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, or 25.

[0026] In the present invention, d is preferably 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10.

[0027] In the present invention, the lightweight, high-strength, heat-resistant, refractory high-entropy alloy is preferably one of the following alloys:

[0028] Ti 42 VxD 23 2nB 25 、Ti 40 Zr 10 V 20 5nN 25 、Ti 38 Zr 12 V 18 7nB 25 、Ti 34 Zr 25 V9Mo7 25 、Ti 36 Zr 25 V9Mo5 25 .

[0029] The present invention regulates Ti a Zr b V c Mo d Nb 25The content of Ti, Zr or Ti, V in refractory high entropy alloys increases the atomic size mismatch of the alloy, causing it to exhibit severe lattice distortion. At the same time, the replacement of a small amount of V by Mo increases the modulus mismatch of the alloy.

[0030] In the present invention, the density of the lightweight refractory high entropy alloy can be as low as 6.2 g / cm 3 , which is much lower than most refractory high entropy alloys. It exhibits good toughness at room temperature and has high strength and good thermal stability at high temperatures.

[0031] The present invention also provides a method for preparing a lightweight, high-strength, heat-resistant, refractory high-entropy alloy, comprising the following steps:

[0032] Take the raw materials in atomic percentage, place them in a crucible from top to bottom for smelting according to their melting points, and smelt them repeatedly N times and then cool them to obtain a lightweight, high-strength, heat-resistant, refractory high-entropy alloy.

[0033] In the present invention, the smelting is carried out under argon protection, and the smelting pressure is -0.03 to -0.01 MPa, preferably -0.02 MPa.

[0034] In the present invention, the smelting power is 90-110 kW, preferably 95-105 kW, and more preferably 100 kW.

[0035] In the present invention, the N is ≥ 5, preferably 6, 7, 8, 9, 10, 11; the cooling time is 15 to 30 minutes, preferably 20 minutes.

[0036] In the present invention, the purity of the raw materials is independently ≥ 99.97%.

[0037] In the present invention, in order to meet the requirements of lightweight, and also to ensure the toughness of refractory high entropy alloys at room temperature. The present invention takes four alloying elements "Ti, Zr, V, Mo, Nb" with relatively low density, and in order to prevent the formation of brittle V2Zr-Laves intermetallic phase, by regulating the content of Ti, Zr or Ti, V elements, and replacing part of V with high modulus Mo, a low-density single-phase BCC high-entropy alloy is prepared. The large atomic size Zr element replaces the Ti element or the Ti element replaces the smaller size V element, which increases the atomic size mismatch of the alloy, causing the alloy to show severe lattice distortion. At the same time, the high modulus Mo element replaces a small amount of V elements with similar size to further increase the modulus mismatch of the alloy, thereby showing higher toughness at room temperature, and at the same time, showing high strength and good thermal stability at high temperatures.

[0038] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0039] Example 1

[0040] Lightweight, high strength and heat resistant Ti 42 VxD 23 2nB 25 The preparation steps of refractory high entropy alloy are as follows: use Ti, Zr, V, Mo, Nb with a purity of not less than 99.97wt.% as raw materials, wash and dry the raw materials with anhydrous ethanol, place the dried raw materials in a water-cooled copper crucible, put the raw materials with low melting points in the lower part, and the raw materials with high melting points in the upper part. When the vacuum degree in the smelting furnace reaches 5×10 -3 Pa, high-purity argon gas was flushed in for 3 times of gas washing. After the gas washing, the pressure in the chamber was guaranteed to be -0.02MPa. Smelting began with a smelting power of 90kW. To ensure uniform composition, after one smelting, the alloy block was taken out after cooling and then inverted for secondary smelting. The smelting was repeated 6 times. The final cooling time was 20 minutes, and the alloy block was taken out after cooling.

[0041] The cast sample prepared by this method has a single-phase BCC structure. The alloy density is 6.2g / cm 3 , which is much lower than most refractory high entropy alloys; the alloy has an atomic size mismatch of 3.8%, a tensile strength of about 930 MPa at room temperature, and a specific strength of about 150 MPa cm above a tensile strain of 15%. 3 / g, the alloy hardness value exceeds 350HV. At the same time, it has good thermal stability and high strength at 800℃, showing a compressive strength of about 680MPa and a compressive strain of more than 40%.

[0042] Example 2

[0043] Lightweight, high strength and heat resistant Ti 40 Zr 10 V 20 5nN 25 The preparation steps of refractory high entropy alloy are as follows: use Ti, Zr, V, Mo, Nb with a purity of not less than 99.97wt.% as raw materials, wash and dry the raw materials with anhydrous ethanol, place the dried raw materials in a water-cooled copper crucible, put the raw materials with low melting points in the lower part, and the raw materials with high melting points in the upper part. When the vacuum degree in the smelting furnace reaches 5×10 -3 Pa, high-purity argon gas was flushed in for 3 times of gas washing. After the gas washing, the pressure in the chamber was guaranteed to be -0.02MPa. Smelting began with a smelting power of 100kW. To ensure uniform composition, after one smelting, the alloy block was taken out after cooling and then put in upside down for secondary smelting. The smelting was repeated 7 times. The final cooling time was 20 minutes, and the alloy block was taken out after cooling.

[0044] The cast sample prepared by this method has a single-phase BCC structure. The alloy density is 6.3g / cm 3 , which is much lower than most refractory high entropy alloys; the alloy has an atomic size mismatch of 4%, a tensile strength of about 950MPa at room temperature, and a specific strength of more than 150MPa·cm over a tensile strain of 13%. 3 / g, the alloy hardness value exceeds 360HV. At the same time, it has good thermal stability and high strength at 800℃, showing a compressive strength of about 690MPa and a compressive strain of more than 40%.

[0045] Example 3

[0046] Lightweight, high strength and heat resistant Ti 38 Zr 12 V 18 7nB 25 The preparation steps of refractory high entropy alloy are as follows: use Ti, Zr, V, Mo, Nb with a purity of not less than 99.97wt.% as raw materials, wash and dry the raw materials with anhydrous ethanol, place the dried raw materials in a water-cooled copper crucible, put the raw materials with low melting points in the lower part, and the raw materials with high melting points in the upper part. When the vacuum degree in the smelting furnace reaches 5×10 -3 Pa, high-purity argon gas was flushed in for 3 times of gas washing. After the gas washing, the pressure in the chamber was guaranteed to be -0.02MPa. Smelting began with a smelting power of 100kW. To ensure uniform composition, after one smelting, the alloy block was taken out after cooling and then put in upside down for secondary smelting. The smelting was repeated 5 times. The final cooling time was 20 minutes, and the alloy block was taken out after cooling.

[0047] The as-cast sample prepared by this method has a single-phase BCC structure; the alloy density is 6.4g / cm 3 , which is much lower than most refractory high entropy alloys; the alloy has an atomic size mismatch of 4.2%, a tensile strength of about 950 MPa at room temperature, and a specific strength of more than 148 MPa cm above a tensile strain of 10%. 3 / g, the alloy hardness value exceeds 360HV. At the same time, it has good thermal stability and high strength at 800℃, showing a compressive strength of about 700MPa and a compressive strain of more than 45%.

[0048] Example 4

[0049] Lightweight, high strength and heat resistant Ti 34 Zr 25 V9Mo7 25The steps for preparing refractory high entropy alloys are as follows: Use Ti, Zr, V, Mo, and Nb with a purity of not less than 99.97wt.% as raw materials, wash and dry the raw materials with anhydrous ethanol, place the dried raw materials in a water-cooled copper crucible, place the raw materials with low melting points in the lower part, and the raw materials with high melting points in the upper part. When the vacuum degree in the smelting furnace reaches the required 5×10 -3 Pa, high-purity argon gas was flushed in for 3 times of gas washing. After the gas washing, the pressure in the chamber was guaranteed to be -0.02MPa. Smelting began with a smelting power of 110kW. To ensure uniform composition, after one smelting, the alloy block was taken out after cooling and then put in upside down for secondary smelting. The smelting was repeated 6 times. The final cooling time was 20 minutes, and the alloy block was taken out after cooling.

[0050] The as-cast samples prepared by this method have a single-phase BCC structure, such as Figure 1 XRD pattern shown; Figure 2 No precipitated phase was found in the TEM image. The selected area electron diffraction pattern in the upper right corner shows that it is a single-phase BCC structure, which is consistent with the XRD results. The alloy density is about 6.5g / cm 3 , much lower than most refractory high entropy alloys; the alloy has the highest atomic size mismatch, 5.2%. The tensile strength at room temperature is about 1050MPa, exceeding 16% tensile strain, such as Figure 3 As shown. Specific strength exceeds 160MPa·cm 3 / g, the alloy hardness value exceeds 380HV. At the same time, it has good thermal stability and high strength at 800℃, showing a compressive strength of about 720MPa and a compressive strain of more than 45%.

[0051] Example 5

[0052] Lightweight, high strength and heat resistant Ti 36 Zr 25 V9Mo5 25 The steps for preparing refractory high entropy alloys are as follows: Use Ti, Zr, V, Mo, and Nb with a purity of not less than 99.97wt.% as raw materials, wash and dry the raw materials with anhydrous ethanol, place the dried raw materials in a water-cooled copper crucible, place the raw materials with low melting points in the lower part, and the raw materials with high melting points in the upper part. When the vacuum degree in the smelting furnace reaches the required 5×10 -3 Pa, high-purity argon gas was flushed in for 3 times of gas washing. After the gas washing, the pressure in the chamber was guaranteed to be -0.02MPa. Smelting began with a smelting power of 110kW. To ensure uniform composition, after one smelting, the alloy block was taken out after cooling and then put in upside down for secondary smelting. The smelting was repeated 8 times. The final cooling time was 20 minutes, and the alloy block was taken out after cooling.

[0053] The as-cast sample prepared by this method has a single-phase BCC structure; the alloy density is 6.4g / cm 3 , which is much lower than most refractory high entropy alloys; the alloy has an atomic size mismatch of 5.1%, a tensile strength of about 1000 MPa at room temperature, and a specific strength of more than 156 MPa cm above a tensile strain of 10%. 3 / g, the alloy hardness value exceeds 380HV. At the same time, it has good thermal stability and high strength at 800℃, showing a compressive strength of about 710MPa and a compressive strain of more than 40%.

[0054] It can be seen from the above embodiments that the present invention provides a lightweight, high-strength, heat-resistant, refractory high-entropy alloy and a preparation method thereof. In order to obtain excellent mechanical properties at room temperature and high temperatures, the present invention considers solid solution strengthening from the perspective of improving the atomic size mismatch of the alloy, so that it exhibits severe lattice distortion, and relies on solid solution strengthening to provide toughness at room temperature. At the same time, the high modulus Mo replaces part of the V with a similar atomic size, further increasing its modulus mismatch, so that it can maintain high strength and thermal stability at high temperatures.

[0055] The light refractory high entropy alloy of the present invention has a relatively low density of the selected alloying elements. The large atomic size Zr element replaces the Ti element or the Ti element replaces the smaller size V element, and the high modulus Mo element replaces a small amount of V element, forming a single-phase BCC light refractory high entropy alloy, which maintains the toughness of the alloy at room temperature and the high strength and thermal stability at high temperature through solid solution strengthening. The preparation operation of the light refractory high entropy alloy is simple, the preparation is pollution-free, and the experimental energy consumption is low. It also solves the problems of high density and poor room temperature plasticity of refractory high entropy alloys, and has broad application prospects in the fields of chemical industry, metallurgy and nuclear power.

[0056] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A lightweight, high-strength, heat-resistant, refractory high-entropy alloy, characterized in that: The lightweight, high-strength, heat-resistant, refractory high-entropy alloy is denoted by Ti in terms of atomic percentage. a Zr b V c Mo d Nb 25 , where 25≤a≤45, 5≤b≤25, 5≤c≤25, 0≤d≤10 and a+b+c+d=75.

2. The lightweight, high-strength, heat-resistant, refractory high-entropy alloy according to claim 1, characterized in that: The lightweight, high-strength, heat-resistant, refractory high-entropy alloy is selected from one of the following alloys: The 42 Zr8V 23 Mo2Nb 25 ,The 40 Zr 10 V 20 Mo5Nb 25 ,The 38 Zr 12 V 18 Mo7Nb 25 ,The 34 Zr 25 V9Mo7Nb 25 ,The 36 Zr 25 V9Mo5Nb 25 。 。 3. The method for preparing a lightweight, high-strength, heat-resistant, refractory high-entropy alloy according to claim 1 or 2, characterized in that: The following steps are involved: Take the raw materials in atomic percentage, place them in a crucible from top to bottom for smelting according to their melting points, and smelt them repeatedly N times and then cool them to obtain a lightweight, high-strength, heat-resistant, refractory high-entropy alloy.

4. The preparation method according to claim 3, characterized in that: The smelting is carried out under argon protection, and the smelting pressure is -0.03 to -0.01 MPa.

5. The preparation method according to claim 3 or 4, characterized in that: The smelting power is 90-110 kW.

6. The preparation method according to claim 5, characterized in that: The N is ≥ 5, and the cooling time is 15 to 30 minutes.

7. The preparation method according to claim 3, 4 or 6, characterized in that: The purity of the raw materials is independently ≥ 99.97%.

Citation Information

Cited By

  • A lightweight, high-strength, high-temperature-resistant high-entropy alloy and its preparation method and application

    CN120249776B